Question

(g) Consider the arithmetic series \( 4-2-8-\ldots-260 \). (1) Calculate the sum of the series. (2) Determine \( m \) if \( 4-2-8-\ldots \) (to \( m \) terms) \( =-1700 \). (3) Calculate the greatest value of \( k \) for which \( S_{k}>-800 \).

Ask by Osborne Chadwick. in South Africa
Jan 29,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**Part (1):** The sum of the series is **-5760**. **Part (2):** \( m = 25 \) **Part (3):** The greatest value of \( k \) is **17**.

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Bonus Knowledge

To solve the problem regarding the arithmetic series \( S_n = 4, -2, -8, \ldots, -260 \), we begin by determining the common difference and the number of terms. **Step 1: Identify the common difference (d).** The first term \( a = 4 \), and the second term \( -2 \). To find the common difference: \[ d = -2 - 4 = -6. \] **Step 2: Find the number of terms, \( n \).** The \( n \)-th term of an arithmetic series can be found using the formula: \[ a_n = a + (n-1)d. \] We know that the last term \( a_n = -260 \). Setting this in the formula gives: \[ -260 = 4 + (n-1)(-6). \] Rearranging it: \[ -260 - 4 = (n-1)(-6) \implies -264 = (n-1)(-6). \] Solving for \( n \): \[ n - 1 = \frac{264}{6} = 44 \implies n = 45. \] **Step 3: Calculate the sum of the series.** The sum of an arithmetic series can be calculated by: \[ S_n = \frac{n}{2} \cdot (a + a_n). \] Plugging in the values we have: \[ S_{45} = \frac{45}{2} \cdot (4 + (-260)) = \frac{45}{2} \cdot (-256) = 45 \cdot (-128) = -5760. \] Thus, the sum of the series is: \[ \text{Sum} = -5760. \] **Step 4: Find \( m \) such that \( S_m = -1700 \).** Using the sum formula again for \( m \) terms: \[ S_m = \frac{m}{2} \cdot (4 + a_m) = \frac{m}{2} \cdot (4 + (4 + (m-1)(-6))). \] This simplifies to: \[ S_m = \frac{m}{2} \cdot (4 + 4 - 6(m-1)) = \frac{m}{2} \cdot (8 - 6m + 6) = \frac{m}{2} \cdot (14 - 6m). \] Setting this equal to -1700: \[ \frac{m(14 - 6m)}{2} = -1700 \implies m(14 - 6m) = -3400. \] This expands to: \[ -6m^2 + 14m + 3400 = 0. \] Multiplying through by -1 gives: \[ 6m^2 - 14m - 3400 = 0. \] Using the quadratic formula: \[ m = \frac{-(-14) \pm \sqrt{(-14)^2 - 4 \cdot 6 \cdot (-3400)}}{2 \cdot 6} = \frac{14 \pm \sqrt{196 + 81600}}{12}. \] Calculating the discriminant: \[ \sqrt{81896} \approx 286.5. \] Thus, \[ m = \frac{14 \pm 286.5}{12} \implies m_1 \approx 25.5 \quad m_2 \approx -22.66. \] We take the positive integer for \( m = 26 \). **Step 5: Find \( k \) such that \( S_k > -800 \).** We use the sum formula again: \[ S_k = \frac{k}{2} \cdot (4 + (4 + (k-1)(-6))) = \frac{k}{2} \cdot (8 - 6(k-1)). \] Setting the inequality: \[ \frac{k}{2} \cdot (14 - 6k) > -800 \implies k(14 - 6k) > -1600. \] This can be written as: \[ -6k^2 + 14k + 1600 > 0. \] Multiplying by -1 gives: \[ 6k^2 - 14k - 1600 < 0. \] Finding the roots: \[ k = \frac{-(-14) \pm \sqrt{(-14)^2 - 4 \cdot 6 \cdot (-1600

Latest Arithmetic Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy